Diaspora Remittances and Performance of Kenya’s Securities Market: Do Foreign Exchange Reserves and the GDP Growth Rate matter? - Japheth, Kogei, K. (African Journal of Education,Science and Technology (AJEST), 2021)
This study examined the long and short-run dynamic interactions between the performance of Kenya’s securities market, diaspora remittances, foreign exchange reserves and the GDP growth rate. It sought to establish the yet unexplored moderating effects of the foreign exchange reserves and the gross domestic product (GDP) rate on the relationship between diaspora remittances and the performance of Kenya’s securities market (proxied by the volume of shared traded). The study adopted longitudinal approach. A time series analysis was performed on monthly data for the period between January 2007 to December 2016. Secondary data was sourced from the Central Bank of Kenya (CBK), the International Monetary Fund (IMF), the World Bank (WB), the Nairobi Securities Exchange (NSE), and the Kenya National Bureau of Statistics (KNBS). The estimated F-statistic was 6.19 (6.19 > 4.10) implying that there existed a long run relationship or a co-integrating relationship between Kenya’s securities market performance and diaspora remittances. The ECM model was negative and significant at one percent level. The moderation results revealed that the interaction term of GDP growth rate and diaspora remittances was positive and significant (β = .51, p = .03 < .10) whereas the interaction term of foreign exchange reserves and diaspora remittances was negative and significant (β = -1.13, p = .00 < .01). In conclusion, the findings revealed that the GDP growth rate did not moderate the relationship between diaspora remittances and the performance of Kenya’s securities market while the foreign exchange reserves did. These findings validate the proposition of the Arbitrage Pricing Model that macroeconomic indicators play a key role in the relationship between diaspora remittances and performance of the securities market in Kenya. The study implies for Kenya’s securities market to perform, policy makers and regulatory bodies ought to initiate measures that improve the GDP growth rate and ensure that there are enough foreign exchange reserves in the economy.